PERENCANAAN STRUKTUR RANGKA ATAS JEMBATAN RANGKA BAJA PADA GAMPONG LEUBOK PEMPENG KECAMATAN PEUREULAK KABUPATEN ACEH TIMUR - Muhammad Ridha; Khairul Miswar (Politeknik Negeri Lhokseumawe, 2016)
Steel frame bridge Gampong Leubok Pempeng districs Peureulak counties Aceh Timur is a connecting Leubok Pempeng village to Alue Batee village and others village in the peureulak districts with spans of 30 meters and width of 7 meters and including class B. This thesis aims to plan for building a bridge over a steel frame using a standard warren type which includea backrest, sidewalk, the vehicle floor plate, longitudinal girder, cross girder, main frame and bolt connection. To plan the loading bridge using RSNI T-02-2005 and steel structural design using RSNI T-03-2005, the calculation method using LRFD. Results obtained plannin backrest pipe diameter 48,6 mm, sidewalk of 25 cm thick reinfored concrete fc’ 25 Mpa, reinforced cocnrete slab 20 cm and the quality of steel profiles longitudinal girder using steel profiles H 350 x 175 x 7 x 11, cross girder using steel profiles H 488 xx 300 11 x 18. Top wind bracing using steel profiles H 125 x 125 x 6,9 x 9 and profiles L 125 x 125 x 12, while lower wind bracing using steel profiles L 125 x 125 x 12. Frame force calculated with matri method. Rods up, lower and diagonal using steel profiles H 300 x 300 x 10 x 15. Connecting bolts type A-325 diameter 1 inch and ½ inch. Longitudinal girder deflection is 3,130 mm 8,333 mm, cross girder deflections is 1,002 cm 2 cm and deflection in the main frame is 3,12 cm smaller than the allowable deflection 12,5 cm.Keyword : steel frame bridge, Matrix method